The Curious Case of the Glowing Bones - Taylor, Stephanie (Journal of Interdisciplinary Science Topics, 2017)
In the FOX television series Bones a set of remains are discovered that are blue and glowing. It was determined that the bones were glowing due to the presence of a Vibrio phosphoreum, which is a bioluminescent bacteria. This paper looks into whether or not the V. phosphoreum could have been introduced into the victim’s body and survived long enough to be present when the remains were found.